PREFERENSI MENONTON DRAMA KOREA PADA REMAJA - Topan, Diva Aulia; Ernungtyas, Niken Febrina (Universitas Prof. Dr. Moestopo (Beragama), 2020)
This research discusses the contribution of the ?Hallyu? (Korean Wave) on the increasing number of Korean drama consumption among high school students in order the daily and academic life. The aim of the research is to describe the preference of high school students watching the Korean drama. Data were collected through in-depth interview on three informants. The informants are high school students who had been selected and determined using a purposive sampling technique based on the criteria of inclusion in this study. In the process of this assessment, it was discovered that the Hallyu phenomenon in Indonesia contributes to increasing interest in watching Korean dramas. The three informants interviewed had an interest, a habit of watching and a different mood change experience when consuming Korean dramas. In addition, the three informers also give a statement that they agree that consuming Korean drama in everyday life does not affect their academic performance. Therefore, it can be concluded that Hallyu has contributed to the increasing consumption of Korean dramas by high school students but it does not cause changes to their daily routine, including their academic performance.